ANALYSIS OF EXTENDED ELASTIC IMPEDANCE (EEI) INVERSION RESULTS WITH VARIOUS AVO EQUATIONS MARMOUSI2 CASE STUDY - MAULIDYA SWARI (NIM: 12313039), FIRDHA
Seismic inversion of the reservoir model for hydrocarbons can be further characterized. During seismic inversion, one of the known methods is Extended Elastic Impedance (EEI). This method creates a certain trace of the elastic parameters directly. In this method, the trace can be obtained by AVO equations. This research uses two equations of AVO i.e. Shuey 1985 and Ursenbach & Stewart 2008. Using two differential AVO equations is used to figure out the best AVO equation for seismic inversion of EEI using 2D Marmousi2 data. Gather data is used for AVO analysis and partial angle stack data is used for seismic inversion with a well to control inversion. Based on the sensitivity analysis, sensitive parameters to reservoar zone is Lambda-Rho. Trace of EEI reflectivity for these parameters can be generated by the extraction certain information based on AVO equation. In addition, it also uses a certain angle of EEI (χ) of the highest correlation with initial log. AVO equation will produce a different volume reflectivity of Lambda-Rho vary at time of inversion.